Curriculum design and development in higher music education. Handbook by Jeremy Cox - Polifonia Working Group (Polifonia, 2007)
This working gourp (WG) has focused on quality enhancement in relation to the role of research in higher music education (HME) institutions. It has paid particular attention to the kind of research described as artistic research. In doing so, it has examined the role of students as participants in this area, especially at Masters and Doctoral level, as well as considering how best to support the on-going professional development of conservatoire teachers as artistic researchers. The solid establishment of a European Platform for Artistic Research in Music has been one of its means of achieving this. After a pilot event in Belgrade in 2010, the first conference of this platform within the lifetime of the project took place in Rome (May, 2012) and was followed by two further events (Lyon, April 2013 and Stockholm, March 2014).